ON FUNDAMENTAL SOLUTIONS OF ORDINARY DIFFERENTIAL EQUATIONS OF THE SECOND ORDER WITH THE BESSEL OPERATOR (Scientific journal of the Fergana State University, 2020)
In the article, the method of finding the fundamental solution of an ordinary differential equation with the Bessel operator is described.